PENGARUH PENERAPAN COOPERATIVE LEARNING TIPETHE POWER OF TWO AND FOUR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 22 PADANG - Rahmi, Rahmi; Saputri, Vina Delfia (Prodi Pendidikan Matematika, 2013)
TheÂ  purposeÂ  ofÂ  thisÂ  researchÂ  isÂ  toÂ  knowÂ  whetherÂ  studentsâÂ  understandingÂ  of mathematics concept by using Cooperative Learning of The Power of two and Four typeÂ  isÂ  isÂ  betterÂ  thanÂ  studentsâÂ  understandingÂ  ofÂ  mathematicsÂ  conceptÂ  byÂ  using conventionalÂ  methodÂ  forÂ  studentÂ  garadeÂ  VIIÂ  ofÂ  SMPNÂ  22Â  Padang.Â  TheÂ  kindÂ  of Â this research is experimental research. The sample of this research is student in class VII 6 and VII 7. The instrument of this research is final test in essay form which consists of Â indicator of concept understanding. The reliability of the test is0.71.Based on the data analysis, it is found that the meanscore of the test related toÂ  studentsâ understanding of mathematics concept in experimental class isÂ  77.31 and it is higher than control class that is 69.59. Hypothesis testing by using t-test found that p-value 0.015 is lower than Î±= 0,05. It can be concluded that studentsâ understandingÂ  of mathematics concept by using Cooperative Learning of The Power of Two and FourÂ  typeÂ  isÂ  betterÂ  thanÂ  studentsâÂ  understandingÂ  ofÂ  mathematicsÂ  conceptÂ  byÂ  using conventional method.